Development of the West and the US Army - Edward Bowie (Symphony in the Flint Hills, 2013)
In spite of romantic notions of the taming of the “Wild West,” a realistic picture of the frontier Army provides a more insightful understanding of its seminal role in the development of the American West.
Keywords: wild west; pioneer; prairie; grassland; adventure; travel; westward; army; military; territory; Native American; Indian; people; tribe; Great Plains; explore; Santa Fe Trail; Oregon Trail; wagon; frontier; Cheyenne Indians; Union Pacific Railroad; attack; Fossil Creek; Mexican Comancheros; Mormon separatists; Kansas Jayhawkers; Missouri Border Ruffians; Fort Leavenworth; Civil War; Bleeding Kansas; expansion